2020
DOI: 10.1590/1980-5373-mr-2019-0570
|View full text |Cite
|
Sign up to set email alerts
|

Austenitizing Temperature and Cooling Rate Effects on the Martensitic Transformation in a Microalloyed-Steel

Abstract: The effects of the austenitizing temperature and the cooling rate upon the kinetic of athermal martensitic transformation in a microalloyed steel were evaluated. Considering the studied steel, the knowledge about these effects on the martensitic transformation has a great relevance for naval manufacturers and steel researchers. In this study, computational simulation was performed aiming to evaluate the phase's stability. Specimens were submitted to quenching simulations in a dilatometer, considering four diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 19 publications
0
4
0
14
Order By: Relevance
“…A significant decrease in M s temperature was observed as the step time increased. One factor that strongly influences this temperature is the austenite carbon content 34,35 , so that the higher the austenite carbon content, the lower its M s temperature. Thus, the decrease in M s temperature with the increase of step time, indicates the occurrence of carbon partition for austenite due to ferrite formation in the step stage.…”
Section: Martensite Start Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…A significant decrease in M s temperature was observed as the step time increased. One factor that strongly influences this temperature is the austenite carbon content 34,35 , so that the higher the austenite carbon content, the lower its M s temperature. Thus, the decrease in M s temperature with the increase of step time, indicates the occurrence of carbon partition for austenite due to ferrite formation in the step stage.…”
Section: Martensite Start Temperaturementioning
confidence: 99%
“…However, the carbon partition for austenite due to the ferrite formation in an intercritical annealing, can lead to a non-homogeneous austenite carbon profile, as discussed by Tan et al 6 and Santofimia et al 36 , influencing the retained austenite morphology and the occurrence of the TRIP effect during deformation 39 . The M s temperature determination after the SQ treatment is necessary to guarantee great agreement between the thermodynamic predictions and the real Q&P heat treatments, since this M s value can be considered an indirect measurement of the austenite carbon content prior to the partial quenching in a Q&P cycle 35 .…”
Section: Martensite Start Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…A melhor condição de ataque foi com 1,5mL de HCl (60 segundos). Esse aço pode ser classificado como um aço de alta resistência baixa liga, comumente empregado na indústria naval [17]. Ele possui adições de Cr e Mo que são bons formadores de carbonetos.…”
Section: Avaliação Das Micrografias Obtidas Para Cada Condição De Ataqueunclassified
“…The issue of the effect of cooling rate on T Ms in the process of quenching carbide-containing steels was discussed in a number of publications. Authors of [22] have found that in the case of low-alloy high-strength steels, lower values of T Ms corresponded to higher specimen cooling rates. They assumed that at lower values of the cooling rate, precipitation of chromium and molybdenum carbides become possible.…”
Section: Introductionmentioning
confidence: 99%